The Impact of Professional Development on K–12 Teacher Awareness, Use, and Perceptions of OER - Arispe, Kelly; Hoye, Amber; Haynes, Meagan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
This paper reports the findings from cycles three and four in a longitudinal design-based research (DBR) study with K–12 teachers to evaluate their gains in awareness, use, and perceptions about open educational resources (OER) in general and after engaging with the Pathways Project (PP), a repository of 900 world language activities. Two groups of teachers participated in distributed learning with different engagement levels to apply the 5Rs of OER (i.e., retain, reuse, revise, remix, and redistribute), specifically using OER from the PP. The Pathways subscribers (n = 23) attended webinars and received monthly newsletters throughout the project period. A smaller group, referred to as the Pathways training cohort (n = 16), participated in a four-month cohort including a synchronous workshop, monthly synchronous meetings, and asynchronous tasks. The study was conducted in the Mountain West region of the United States, where access to quality teaching materials varies across rural and urban districts, and professional development (PD) opportunities are lacking. The findings revealed that the training cohort self-reported statistically significant increases in awareness of all 5Rs, and increased frequency of revising and remixing OER; their belief in the effectiveness of OER for learning also increased. Conversely, while the subscribers group did show some gains in awareness, use, and perceived value of OER, none of these were statistically significant. These findings suggested that K–12 teachers valued OER but require strategic, long-term PD to achieve gains in awareness, use, and perceived value of OER. This study responded to the challenge of sustaining open pedagogy, particularly for an under-studied K–12 population.